POSTMODERNISM: A STEP IN AN "INEXACT DIRECTION" - I. N. Krizhanovskiy (Российский технологический журнал)
The article is devoted to the consideration and understanding of postmodernism in the context of its impact on various spheres of society. The author attempts to answer the question of how the onset of a new semantic era coupled with the development of information technologies will affect the state of the society in general and the scientific sphere in particular. The impact of this phenomenon on culture, art (in view of the breadth of the concept, only literature is chosen), social life and science is discussed. Based on the analysis of scientific, publicistic and artistic literary sources, as well as materials from the media, the nature of the trends induced by the sociocultural phenomenon under discussion is established. The author of the article analyzes the works of both apologists of postmodernism (for example, R. Bart, M. Foucault, I. Skoropanova, V. Erofeev) and opponents (for example, J. Baudrillard, A. Dugin, V. Stepin, S. Kara-Murza). We consider relatively new phenomena directly related to the predominance of the philosophical principles of postmodernism in the world information field (for example, “columbiners”, clip thinking, postdemocracy, and some others). The article assesses the attitude of postmodernism to traditional culture and values. The author ascertains the mediated nature of its influence on scientific activity and leans towards a negative assessment of postmodernism (in its present form) as the main ideological principle.